2010
DOI: 10.1002/anie.200906720
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric Sensing of Neutral Species Based on a Uniform‐Sized Molecularly Imprinted Polymer as a Receptor

Abstract: Polymeric membrane ion-selective electrodes (ISEs) have been routinely used for determination of ionic species in clinical applications and for the determination of water quality owing to their attractive features including excellent selectivity, low cost, ease of use, and high reliability. [1][2][3] This well-established analytical technology has undergone a quiet revolution over the last few years. The detection limits of ISEs have been lowered from the micromolar to the subnanomolar range, and the discrimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 113 publications
(73 citation statements)
references
References 33 publications
1
71
0
1
Order By: Relevance
“…As shown in Fig.1a, the MIP beads are spherical with a diameter distribution of 0.5-1.0 ȝm. As previously reported by our group [10] , the uniform-sized beads can be well dissolved in the polymeric ISE membrane, which could cause more binding sites available in the membrane and lower membrane impedance. Indeed, the membrane ISE prepared with the uniform clenbuterol MIP beads showed a shorter response time and lower noise levels.…”
Section: Characterization Of Mip and Nipsupporting
confidence: 57%
“…As shown in Fig.1a, the MIP beads are spherical with a diameter distribution of 0.5-1.0 ȝm. As previously reported by our group [10] , the uniform-sized beads can be well dissolved in the polymeric ISE membrane, which could cause more binding sites available in the membrane and lower membrane impedance. Indeed, the membrane ISE prepared with the uniform clenbuterol MIP beads showed a shorter response time and lower noise levels.…”
Section: Characterization Of Mip and Nipsupporting
confidence: 57%
“…However, very few ISEs have been developed for direct recognition of neutral species [2]. In recent years, it has been found that undissociated neutral phenols could generate anionic potential responses using poly(vinyl chloride) (PVC) liquid membranes doped with lipophilic nitrogen-containing compounds and metal porphyrins [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The resulting polymer was dried for 10 h in vacuum at 50 • C. Non-imprinted polymer (NIP) was prepared under identical conditions except for omission of the template. Traditional MIP microbeads were prepared according to the precipitation method described before [16].…”
Section: Synthesis Of Triclosan Mipmentioning
confidence: 99%
“…As generic and highly successful approaches to chemical sensing, potentiometric sensors have shown to be very promising for trace-level environmental and biological measurements [10,11]. Nowadays, potentiometric sensors based on MIPs have been successfully developed for determination of anions, cations and neutral species [12][13][14][15][16]. However, it should be noted that most of the MIPs based potentiometric sensors developed so far have poor detection limits in the micromolar range, which are unsuitable for trace-level measurements, especially with high levels of electrolyte background.…”
Section: Introductionmentioning
confidence: 99%